Eksistensi Penghayat Kepercayaan Kejawen Di Tengah Arus Modernisasi - Setianingsih, Agnes Tutut; Drakel , Julia Kumala Asri; Mely Tri Octavina; Wisnu (The Indonesian Journal of Social Studies, 2023)
One of the local beliefs that has survived to this day is the Javanese belief. Kejawen is one of the ancestral beliefs of the Javanese people who adhere to Javanese teachings and culture. Although until now the belief in kejawen still exists, it is possible that this trust has begun to erode over time. The purpose of this study is to determine the existence of followers of the Kejawen belief in the current modernization era. The research method of library research (library research). The author conducts studies from various sources ranging from historical records, previous journals and the latest mass media. All data obtained is then compiled and studied carefully to find the problems discussed. The results obtained from this study are that some of the practices of Kejawen beliefs are still often carried out, but as time goes by, the Kejawen people experience an existential crisis due to the swift currents of modernization. According to modern society, kejawen is an ancient culture that does not need to be preserved. The focus of society in this modern era is western culture so that in the process of building civilization, slang is the goal of life.